2019
DOI: 10.1128/msystems.00202-19
|View full text |Cite
|
Sign up to set email alerts
|

Network Integrative Genomic and Transcriptomic Analysis of Carbapenem-Resistant Klebsiella pneumoniae Strains Identifies Genes for Antibiotic Resistance and Virulence

Abstract: Global increases in the use of carbapenems have resulted in several strains of Gram-negative bacteria acquiring carbapenem resistance, thereby limiting treatment options. Klebsiella pneumoniae is a common carbapenem-resistant pathogenic bacterium that is widely studied to identify novel antibiotic resistance mechanisms and drug targets. Antibiotic-resistant clinical isolates generally harbor many genetic alterations, and the identification of responsible mutations would provide insights into the molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Identification of resistance and virulence factor by traditional molecular technologies is normally labor intensive. Network analysis has been successfully used to analyze the antibiotic resistance and virulence in selected bacteria (Lee et al, 2019). Here, we use the integrated network analysis to construct a cofunctional network to investigate the resistance and virulence factors in A. baumannii, one of the most threatening bacterial pathogens to humans currently because of its widespread antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of resistance and virulence factor by traditional molecular technologies is normally labor intensive. Network analysis has been successfully used to analyze the antibiotic resistance and virulence in selected bacteria (Lee et al, 2019). Here, we use the integrated network analysis to construct a cofunctional network to investigate the resistance and virulence factors in A. baumannii, one of the most threatening bacterial pathogens to humans currently because of its widespread antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In general, analyzing the network structure and understanding the topological properties could discover novel nodes in the complex biologic system and provide new insights for elucidation of the molecular mechanism (Yan et al, 2018). For example, through a genome-scale co-functional network analysis, Lee et al successfully identified several novel genes associated with antibiotic resistance or virulence in Klebsiella pneumoniae (Lee et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, carbapenem resistance is not often studied at a transcriptomic level, and, when it is, the research almost exclusively examines basal expression levels. 3035 In this work, we profiled the short-term transient transcriptomic responses of a partially carbapenem-resistant clinical isolate of E. coli and used our FAST platform to design PNA that uncovered the importance of multiple systems in the development of this phenotype, including the regulators flhC , hycA , and bolA . Furthermore, by inhibiting hycA , bolA , and dsrB with FAST PNA, we were able to re-sensitize the clinical isolate to sub-MIC carbapenem concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…30, 31 Four recent studies that examined transcriptomic profiles of CRE —Enterobacter cloacae , K. pneumoniae (2), and Escherichia coli —identified less consistent responses, although downregulation of porin genes and upregulation of cell survival and β-lactamase genes were observed. 3235 Of this prior research, only one study 32 attempts to evaluate the transcriptomic response of a resistant Enterobacteriaceae strain under antibiotic challenge, the majority examining only the constitutive gene expression levels of an untreated resistant pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…12 Compounding the general problem of antibiotic resistance are challenges in developing and approving new antibiotics. 13 This has spurred research into understanding resistance mechanisms, 14,15 host defenses, [16][17][18] diagnostics 19 and antibiotic generation. 20,21 Ultimately, without a rapid and perhaps general method to develop new targeted antibiotics, therapies might relapse towards those of the pre-antibiotic era.…”
Section: Introductionmentioning
confidence: 99%